Deletion of Tlr3 reduces acute tolerance to alcohol and alcohol consumption in the intermittent access procedure in male mice - Blednov, Yuri A. (Addict Biol, 2020)
Pharmacological studies implicate toll-like receptor 3 (TLR3) signaling in alcohol drinking. We examined the role of TLR3 in behavioral responses to alcohol and GABAergic drugs by studying Tlr3 (−/−) mice. Because of opposing signaling between TLR3 and MyD88 pathways, we also evaluated Myd88 (−/−) mice. Ethanol consumption and preference decreased in male but not female Tlr3 (−/−) mice during two-bottle choice every-other-day (2BC-EOD) drinking. There were no genotype differences in either sex during continuous or limited-access drinking. Null mutations in Tlr3 or Myd88 did not alter conditioned taste aversion to alcohol and had small or no effects on conditioned place preference. The Tlr3 null mutation did not alter acute alcohol withdrawal. Male, but not female, Tlr3 (−/−) mice took longer than wild-type littermates to recover from ataxia by ethanol or diazepam and longer to recover from sedative-hypnotic effects of ethanol or gaboxadol, indicating regulation of GABAergic signaling by TLR3. Acute functional tolerance (AFT) to alcohol-induced ataxia was decreased in Tlr3 (−/−) mice but was increased in Myd88 (−/−) mice. Thus, MyD88 and TLR3 pathways coordinately regulate alcohol consumption and tolerance to intoxicating doses of alcohol and GABAergic drugs. Despite similar alcohol metabolism and similar amounts of total alcohol consumed during 2BC and 2BC-EOD procedures in C57BL/6J mice, only 2BC-EOD drinking induced tolerance to alcohol-induced ataxia. Ataxia recovery was inversely correlated with level of drinking in wild-type and Tlr3 (−/−) littermates. Thus, deleting Tlr3 reduces alcohol consumption by reducing AFT to alcohol and not by altering tolerance induced by 2BC-EOD drinking.